Transformation of Hotel Food Waste into Animal Feed: Two Operational Periods of the Food for Feed Pilot Unit - Paraskevi Panteli (Proceedings, 2020)
Food waste represents 25−35% of the European Municipal Solid Waste (MSW) [1], thus its diversion into innovative utilization streams is critical for sustainable waste management and the achievement of circularity. [...]